Religious Radicalism: Deconstructing The Interpretation Of The Verse Of Jihad In The Qur'an - Bahruddin Bahruddin (International Journal of Research, 2023)
The purpose of this research is to describe the meaning of jihad in the perspective of the mufassirs, so that this jihad can be interpreted for the Muslim community not only in the form of fighting with physical combat and weapons, but has a deeper meaning than that. This research is a literature study (library research) by collecting data on primary and secondary sources related to the research theme. The results of this study can be concluded, that radical in substance and associated with the content of jihad contextually, the meaning of radicals who use terror activities. Terror can be interpreted as curbing da'wah and not broadcasting da'wah and Islamic law, on the basis that the strength of a Muslim's da'wah rests on the strength of faith, so that in its activities it shows the behaviour of believers to encourage amar ma'ruf and eliminate evil in a ma'ruf manner as well. Therefore, jihad in faith is a condition and situation in which a person will continuously preach in a ma'ruf manner until the evil disappears with the awareness of the perpetrators. Meanwhile, treasure jihad is the spirit of sacrifice in building Islamic law; building mosques in isolated places, donating property to the poor so that they can survive, and other things that require material in building the spread of Islam.